The Experience of Family Support by People in the Recovery of Drug Addiction - Dini Farhana Baharudin; Mohd Zaliridzal Zakaria; Zainol Abidin Ahmad; Rezki Perdani Sawai; Abdul Halim Mohd. Hussin; Sarina Mohamed; Melati Sumari (2024)
Recovery from drug addiction is a life-long process. The aim of this preliminary study was looking at the experiences of family support by people in recovery from drug addiction. This study employs a qualitative format using semi-structured interviews with four recovering drug users. Several themes were identified and discussed in relation to the literature on family support of people in recovery. The results highlight the importance of family support in the recovery of drug addiction. Suggestions and recommendations are also included.